Tissue Inhibitor of Matrix Metalloproteinases-1 Knockdown Suppresses the Proliferation of Human Adipose-Derived Stem Cells - Peihua Zhang; Jin Li; Yawei Qi; Xudong Tang; Jianfeng Duan; Li Liu; Zeyong Wu; Jie Liang; Jiangfeng Li; Xian Wang; Guofang Zeng; Hongwei Liu (Stem Cells International)
Tissue inhibitor of metalloproteinases-1 (TIMP-1) is a multifunctional matrix metalloproteinase, and it is involved in the regulation of cell proliferation and apoptosis in various cell types. However, little is known about the effect of TIMP-1 expression on the proliferation of adipose-derived stem cells (ADSCs). Therefore, TIMP-1 expression in the ADSCs was firstly detected by western blotting, and TIMP-1 gene was knocked down by lentivirus-mediated shRNA. Cell proliferation was then evaluated by MTT assay and Ki67 staining, respectively. Cell cycle progression was determined by flow cytometry. The changes of p51, p21, cyclin E, cyclin-dependent kinase 2 (CDK2), and P-CDK2 caused by TIMP-1 knockdown were detected by western blotting. The results indicated that ADSCs highly expressed TIMP-1 protein, and the knockdown of TIMP-1 inhibited cell proliferation and arrested cell cycle progression at G1 phase in the ADSCs possibly through the upregulation of p53, p21, and P-CDK2 protein levels and concurrent downregulation of cyclin E and CDK2 protein levels. These findings suggest that TIMP-1 works as a positive regulator of cell proliferation in ADSCs.